Dyskinetic and Dystonic Cerebral Palsy - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 1992)
The records of 794 cases of congenital cerebral palsy (CP) seen between 1955 and 1986 in the Cheyne Centre for Children with Cerebral Palsy, Chelsea, London were analyzed.